2017
DOI: 10.1039/c6ra26888a
|View full text |Cite
|
Sign up to set email alerts
|

Dielectric, optical and enhanced photocatalytic properties of CuCrO2 nanoparticles

Abstract: Delafossite CuCrO2 nanoparticles with band gap energy of 3.09 eV and surface area of 235 m2 g−1 were prepared by citrate precursor route showed enhanced catalytic degradation of methylene blue in H2O under the sunlight irradiation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
38
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(41 citation statements)
references
References 61 publications
1
38
0
2
Order By: Relevance
“…In recent years, nano‐structured delafossites were synthesized using various techniques aiming to produce – high surface area materials – for different applications, such as catalysts, water purification, batteries, gas sensors, electro‐catalysts, and p‐type dye‐sensitized solar cells (p‐DSSCs) . Among these, particularly the hydrothermally derived delafossite nano‐particles were shown to be a promising substitute for traditionally used NiO in p‐DSSC photocathode applications .…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, nano‐structured delafossites were synthesized using various techniques aiming to produce – high surface area materials – for different applications, such as catalysts, water purification, batteries, gas sensors, electro‐catalysts, and p‐type dye‐sensitized solar cells (p‐DSSCs) . Among these, particularly the hydrothermally derived delafossite nano‐particles were shown to be a promising substitute for traditionally used NiO in p‐DSSC photocathode applications .…”
Section: Introductionmentioning
confidence: 99%
“…The corresponding mass spectroscopy spectrum revealed that the hydroxyl radicals attacks were concentrated on the three double bonds C=C and C=N above the suffer atom in order to break the cycle 22 . Another study carried out by Tokeer Ahmed on methylene blue photodegradation in the presence of the catalyst CuCrO 2 nanoparticle; shows that the mechanism of degradation is based on the C=C double bonds destruction constituent the two benzene rings at the ends 23 . The same mechanisms have been proposed to methylene blue photodegradation by the TiO 2 -Cu catalyst thin films 24 and vanadium-doped iron oxides nanostructured 25 .…”
Section: Introductionmentioning
confidence: 99%
“…According to the reported data in the literature, the direct and indirect band gaps of CuCrO 2 vary with the processing parameters and measurements in the range of 2.95-3.35 eV and 1.28-2.63 eV, respectively [24]. Although the true value of the band gap of CuCrO 2 has been controversy, it can theoretically absorb light in the visible region and it has been shown to be active under solar light in some applications such as water splitting and depollution via photocatalysis reactions [25][26][27]. Recently, Ahmad et al [27] prepared pure CuCrO 2 nanoparticles via polymeric citrate precursor method and showed that ∼88% methylene blue (MB) dye can be degraded after just 1.5 h on these nanoparticles under natural sun light exposure.…”
Section: Introductionmentioning
confidence: 99%
“…Although the true value of the band gap of CuCrO 2 has been controversy, it can theoretically absorb light in the visible region and it has been shown to be active under solar light in some applications such as water splitting and depollution via photocatalysis reactions [25][26][27]. Recently, Ahmad et al [27] prepared pure CuCrO 2 nanoparticles via polymeric citrate precursor method and showed that ∼88% methylene blue (MB) dye can be degraded after just 1.5 h on these nanoparticles under natural sun light exposure. Nevertheless, there are only a few studies published in the literature on the heterostructures of CuCrO 2 with other semiconductors including CuCrO 2 -ZnO for the reduction of Cr(IV) to Cr(III) [28] and water splitting [29], CuCrO 2 -WO 3 for visible light HCl splitting [30], and CuCrO 2 -TiO 2 for photodegradation of MB under ultraviolet (UV) irradiation [31].…”
Section: Introductionmentioning
confidence: 99%